Effect of guided dual-sensory information on motor learning outcomes based on spatiotemporal dimensions - Liwa Sha; Wen Hsin Chiu (PLoS ONE, 2025)
The effectiveness of instructional information is crucial to enhancing motor learning outcomes. However, few studies have explored the mechanisms of augmented attention-guiding dual-sensory information. Based on the spatiotemporal dimensions of movement staging and movement limb segments, the current study analyzed how guided dual-sensory information affects learning a basketball set shot. A teaching experiment involving 132 middle school students was used to analyze three instructional methods: visual-only (video), visual–auditory (video with narration), and guided dual-sensory information with visual cues (video with narration and markers). Participants learned set shooting over three weeks. The results revealed that (1) All three groups (visual-only, dual-sensory, and dual-sensory with visual markers) exhibited improved movement result performance after training, with the group receiving guided dual-sensory instruction exhibiting substantially superior posttest movement result performance than the group receiving video alone. (2) audiovisual (dual-sensory) information considerably enhanced movement pattern performance, and dual-sensory information with additional visual markers strengthened movement pattern retention and optimized upper-limb movement pattern performance during the preparation stage. (3) Both the group receiving video with narration and the group receiving guided dual-sensory instruction exhibited substantial improvements in motor cognition, with the dual-sensory information with visual cues associated with the strongest facilitation effect on upper-limb cognition during the execution stage. These results reveal that guided dual-sensory information substantially enhances motor learning outcomes in basketball shooting, with required movement guidance of the upper-limb segments being greater than that for other body segments. The findings indicate that for digital instruction in physical education, instruction should include strategically employed guided attention methods and multidimensional combinations of information presentation. This study provides a novel perspective on motor learning and a spatiotemporal framework for understanding the learning process.